Penerapan Pendekatan Konstruktivistik Dalam Pembelajaran Aqidah Akhlak Di Mts Al-Kautsar Depok - Qowim, Agus Nur (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2024)
Aqidah Akhlak is often seen as a boring subject and does not open up enough space for students to be more critical and creative in their learning process. It is not surprising that students become lazy and less enthusiastic about taking this subject. So a teacher must choose the right learning methods and approaches that not only make the learning process interesting but also provide space for students to be creative and actively involved throughout the learning process. Until now, various efforts have been made to develop a moral aqidah learning system, one of which is by adapting the learning style through a constructivist approach that is adapted to the characteristics of the moral aqidah itself. The constructivist approach is an activity that allows students to build their own thoughts with their knowledge. From the above phenomenon, researchers are interested in conducting research on the application of a constructivist approach in students of moral aqidah at MTS Al-Kautsar Depok, the factors that support and hinder and the efforts made to overcome the problems faced.